Bridging Ethnoscience and Socio-Scientific Issues: The Role of Interactive Web Media in Scientific Literacy - Mochammad Yasir; Mochammad Ahied; Erlina Wardani; Binar Kurnia Prahani; Üyesi Muhammed Akif Kurtulus (Yayasan Keluarga Guru Mandiri, 2026)
Students' poor scientific literacy in addressing socio-scientific issues is a critical challenge in 21st century science education. Innovative learning approaches are needed to meaningfully integrate ethnoscience, socio-scientific issues, and digital technology. This study investigates the effectiveness of interactive web-based learning integrating Ethnoscience and Socio-Scientific Issues (ESSI) in improving students’ scientific literacy. Using a quasi-experimental non-equivalent control group pretest–posttest design. Scientific literacy was measured using validated tests and analyzed through independent sample t-tests and N-Gain analysis. The results showed that the experimental group achieved significantly higher scientific literacy than the control group (mean posttest = 82.40 vs. 74.15; p = 0.002), with a high N-Gain score of 0.71. The results show that web-based ESSI learning effectively enhances scientific literacy. The study concludes that interactive web-based ESSI learning effectively strengthens students’ scientific literacy. This research contributes to science education by demonstrating the pedagogical value of integrating local wisdom, socio-scientific contexts, and digital media to support contextual and sustainable science learning aligned with the Sustainable Development Goals (SDGs).